Modulated Visible Light Upconversion for Luminescence Patterns in Liquid Crystal Polymer Networks Loaded with Upconverting Nanoparticles. Issue 4 (27th January 2017) - Ye, Simin; Teng, Yongxin; Juan, Ao; Wei, Jie; Wang, Leyu; Guo, Jinbao
Abstract : A novel and efficient strategy to modulate the luminescence intensity of upconversion nanoparticles for fabricating upconversion luminescence patterns in liquid crystal network composite films is demonstrated. The work provides a new way to make emission‐based liquid crystal displays and optical functional films.